Evaluation of The Implementation of PSAK 102 In Murabahah Financing At KSPPS El Rahma Lombok Rinjani - Cahyadi, Haris; Ali, Moh. Yusron; Muhajir, Ahmad Khofi; Iqbal, M. Haeri; Astini, Yuli (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This study aims to evaluate the implementation of Financial Accounting Standards Statement (PSAK) 102 on murabahah accounting in financing practices at KSPPS El Rahma Lombok Rinjani, focusing on the recognition, measurement, presentation, and disclosure aspects. The study used a descriptive qualitative method through in-depth interviews with the management and the Sharia Supervisory Board, field observations, and documentation studies. The results of the study indicate that the implementation of PSAK 102 is generally in accordance with the provisions of sharia accounting standards, supported by a software-based accounting information system that facilitates consistent recording, reporting, and verification of transactions. Challenges faced include the need for regular system updates, increasing human resource capacity in understanding changes to standards, and developing data-based evaluation indicators to measure compliance. On the other hand, there are opportunities in the form of active support from the Sharia Supervisory Board, as well as the potential for strengthening accounting technology for better efficiency and transparency. The study's conclusion confirms that optimizing technology integration, continuous training, and strengthening the internal control system are strategic steps to ensure a more optimal, transparent, and sustainable implementation of PSAK 102 at KSPPS El Rahma Lombok Rinjani.